EFFECT OF LEVOCARNITINE ON ENDURANCE CAPACITY IN TYPE-2 DIABETIC RATS - Bibi, Yasmeen; Hussain, Muhammad Mazhar; Naz, Raeesa (Journal of Ayub Medical College Abbottabad, 2013)
Background: Carnitine is an essential cofactor for the enzymes transporting long chain fatty acids across mitochondrial membranes for beta oxidation and also modulates the intra-mitochondrial acylCoA/CoA ratio. This study was conducted to determine the effect of levo-carnitine on endurance capacity, skeletal muscle fatigue characteristics and glycogen stores in diabetic rats. Methods: This laboratory based experimental study was conducted in department of Physiology, Army Medical College, Rawalpindi, in collaboration with National Institute of Health (NIH), Islamabad, from June 2009 to July 2010. The study was carried on 60 healthy male Sprague-Dawley rats. Serum creatine phosphorkinase (CPK) levels were measured to exclude skeletal muscle disorder. Rats were fed high fat diet (2 weeks) followed by intra-peritoneal injection of streptozocin (35 mg/kg). On 21st day, after confirmation of type 2 diabetes by measuring plasma glucose and TG/HDL ratio, rats were divided into 2 equal groups; group I (Diabetic) and group II (Carnitine). Group II was administered l-carnitine (200mg/kg) for 6 days. Both groups were further subdivided into 2 equal groups- a (swim group) and b (non-swim group). At end of 4th week, the rats of swim group were subjected to swimming test. The extensor digitorum muscle (EDL) of rats of non-swim group was dissected for evaluation of skeletal muscle fatigue characteristics. The glycogen content of EDL muscle and serum free carnitine (FC) levels of all groups were measured. Results: Carnitine treated rats exhibited improvement in swim time as well as skeletal muscle glycogen stores (p<0.001). Significant improvement was also observed in skeletal muscle fatigue characteristics (p<0.05). Serum free carnitine levels were also significantly raised in carnitine groups; the swim groups showed a lower FC levels as compared to their respective non-swim groups (p<0.001). Conclusion: Levo-carnitine increases the glycogen stores and improves the skeletal muscle fatigue characteristics, leading to improvement in endurance capacity in type 2 diabetic rats. Keywords: type 2 diabetes, levo-carnitine, endurance, skeletal muscle, muscle glycogen store